2019
DOI: 10.1177/2045894019841987
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of right ventricular function in experimental pulmonary hypertension

Abstract: Echocardiography, a non-invasive and cost-effective method for monitoring cardiac function, is commonly used for evaluation and pre-clinical diagnostics of pulmonary hypertension (PH). Previous echocardiographic studies in experimental models of PH are fragmentary in terms of the evaluation of right ventricle (RV) function. In this study, three rodent models of PH: a mouse model of hypoxia-induced PH, a rat model of hypoxia+Sugen induced PH and a rat model of monocrotaline-induced PH, were employed to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…Other investigators have assessed RVWTd and found association with RV weight and pressure, but the range of RVWT has varied widely between these reports. 2024 Our measurements are consistent with those of Urboniene et al., who used the MCT model and the same strain of rats as in our study. 22 Although the ICC measurements for RVWT reflect strong inter-rater reliability, it is not as strong as the ICC for PAAT and PAAT/ET in the derivation phase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other investigators have assessed RVWTd and found association with RV weight and pressure, but the range of RVWT has varied widely between these reports. 2024 Our measurements are consistent with those of Urboniene et al., who used the MCT model and the same strain of rats as in our study. 22 Although the ICC measurements for RVWT reflect strong inter-rater reliability, it is not as strong as the ICC for PAAT and PAAT/ET in the derivation phase.…”
Section: Discussionsupporting
confidence: 92%
“…However, none of the previous studies have validated these echocardiography measures against invasive cut-off values that detect PH in rat models. 2024…”
Section: Discussionmentioning
confidence: 99%
“…These indices were unchanged due to profound right ventricular dysfunction manifested by decreased TAPSE. Attenuated PAAT:ET in RV failure with decreased TAPSE has been reported in models of pulmonary hypertension 28 . As such, we are unable to comment specifically upon pulmonary vascular hemodynamics in this study.…”
Section: Discussionmentioning
confidence: 71%
“…26 PAAT:ET in RV failure with decreased TAPSE has been reported in models of pulmonary hypertension. 28 As such, we are unable to comment specifically upon pulmonary vascular hemodynamics in this F I G U R E 5 Ultrasound lung injury score. Ultrasound images captured at baseline, 1 hour posttreatment and at end of study; scores are represented as mean ± SE for each group.…”
Section: Discussionmentioning
confidence: 91%
“…Hematoxylin and eosin (H&E) staining was performed on the hearts sections. 20 22 The images were scanned using the Pannoramic SCAN system (3DHISTECH, Budapest, Hungary) and analyzed with the Case Viewer software program.…”
Section: Methodsmentioning
confidence: 99%